HGG-56. Spatial mapping of the tumor micro-environment in pediatric glioma. (3rd June 2022) - Messiaen, Julie; Antoranz, Asier; Van Herck, Yannick; Verhaaren, Ben; Nazari, Pouya; Sebastian, Ivey; Milli, Giorgia; Bosisio, Francesca; Pey, Jon; Bempt, Isabelle Vanden; Sciot, Raf; Jacobs, Sandra; et al.
Abstract: High-grade glioma are the main cause of cancer-related death in children. The highly heterogeneous composition of the tumor cells and their interactions with the tumor micro-environment (TME), contribute substantially to the poor response to treatment and the high levels of morbidity and mortality. Here, we used high-dimensional, multiplexed immunohistochemistry to map the single-cell tissue architecture of 26 pediatric glioma samples covering 8 histologic diagnoses, allowing us to determine the spatial distribution of the various tumoral subtypes and how these interact with their local immune-microenvironment. Overall, this analysis showed that tumor grade anti-correlated with the amount of infiltrating cytotoxic T-lymphocytes (CTLs), which were typically more exhausted in the higher grade tumors. In addition, tumor associated macrophages were primarily infiltrating from the blood and presented an M2-like anti-inflammatory phenotype which became more extended with tumor grade. Using the spatial information, possible cell-cell interactions could be determined. In lower grade glioma, we observed an increased activation level of CTLs that were closely located to neighboring T-helper cells. In pediatric glioblastoma, on the other hand, CTLs, even though they were located close to a T-helper cell, could only minimally be activated, and showed more extended exhaustion when residing further away. Additionally, the activation of the CTLs was associated to the distance to the closest PD-L1 positive macrophage in pilocytic astrocytoma and desmoplastic infantile ganglioglioma. In conclusion, with the use of multiplex immunohistochemistry, we are able to study the tumor and TME of pediatric glioma in depth on a single-cell and spatial level, which allows us to further study the heterogeneous landscape of these tumors.